2007
DOI: 10.1111/j.1567-1364.2007.00248.x
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in theRAD27andSGS1genes differentially affect the chronological and replicative lifespan of yeast cells growing on glucose and glycerol

Abstract: The Sgs1 protein from Saccharomyces cerevisiae is a member of the RecQ helicases. Defects in RecQ helicases result in premature aging phenotypes in both yeasts and humans, which appear to be promoted by replicative stress. Yeast rad27 mutants also suffer from premature aging. As the human Rad27p and Sgs1p homologs interact, a similar interaction between the yeast proteins could be important for promoting longevity in S. cerevisiae. We tested the contribution of a potential interaction between Rad27p and Sgs1p … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 33 publications
1
14
0
Order By: Relevance
“…2A), consistent with prior reports that rad27Δ cells lose reproductive capacity at an earlier time point in CLS experiments in unbuffered medium. 26,27 In contrast, rad27Δ cells cultured in buffered SC medium prepared with 10% glucose exhibited a substantially shorter reproductive capacity compared with wild-type cells at day 7, and the reproductive capacity of rad27Δ cells was reduced cells undergoing programmed cell death marked by DNA degradation that resulted in cells with a sub G 1 content of DNA (Fig. 3B).…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…2A), consistent with prior reports that rad27Δ cells lose reproductive capacity at an earlier time point in CLS experiments in unbuffered medium. 26,27 In contrast, rad27Δ cells cultured in buffered SC medium prepared with 10% glucose exhibited a substantially shorter reproductive capacity compared with wild-type cells at day 7, and the reproductive capacity of rad27Δ cells was reduced cells undergoing programmed cell death marked by DNA degradation that resulted in cells with a sub G 1 content of DNA (Fig. 3B).…”
Section: Resultsmentioning
confidence: 98%
“…28 Although sgs1Δ cells have been reported to exhibit a shorter replicative lifespan (RLS) 29 and CLS, 30 it has also been reported that sgs1Δ cells do not exhibit a shorter CLS. 26,31 sgs1Δ cells more frequently undergo adaptive regrowth in stationary phase, which complicates CLS measurements. For example, in early stationary phase, sgs1Δ cells initially exhibit a substantial reduction in reproductive capacity compared with wild-type cells, but at later time points differences in reproductive capacity are masked by adaptive regrowth.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…From genetically manipulated S. cerevisiae strains, large numbers of senescent cells can also be isolated [1820]. From several large scale studies, it has been concluded that replicative and chronological aging are linked [21,22], but other studies in S. cerevisiae involving mutants also suggest that the two are controlled independently [2,2325]. …”
Section: Introductionmentioning
confidence: 99%
“…A contribution of Sgs1 to BER is less likely. Sgs1 functionally interacts with the 5 flap-endonuclease Rad27, which besides its well-understood function in Okazaki fragment maturation also plays a role in long-patch BER [202,209]. Sgs1 also functionally interacts with the ROS-scavenging enzyme Tsa1, which suppresses genome rearrangements and is required for normal growth in the absence of Sgs1 [210].…”
Section: Possible Functions In Excision Repairmentioning
confidence: 99%